Roubekas, N.P. (2019). Theorizing “Religion” in Antiquity - Soneira Martínez, Ramón (ARYS. Antigüedad: Religiones y Sociedades, 2020)
ROUBEKAS, NICKOLAS P. (ed.). (2019). Theorizing “Religion” in Antiquity. Bristol-Sheffield: Equinox Publishing. 458 pp., 129,60€ [ISBN 978-1-7817-9356-5] [Book review]